2006
DOI: 10.1124/mol.106.024836
|View full text |Cite
|
Sign up to set email alerts
|

Boswellic Acids Stimulate Arachidonic Acid Release and 12-Lipoxygenase Activity in Human Platelets Independent of Ca2+and Differentially Interact with Platelet-Type 12-Lipoxygenase

Abstract: Boswellic acids inhibit the transformation of arachidonic acid to leukotrienes via 5-lipoxygenase but can also enhance the liberation of arachidonic acid in human leukocytes and platelets. Using human platelets, we explored the molecular mechanisms underlying the boswellic acid-induced release of arachidonic acid and the subsequent metabolism by platelet-type 12-lipoxygenase (p12-LO). Both ␤-boswellic acid and 3-O-acetyl-11-keto-boswellic acid (AKBA) markedly enhanced the release of arachidonic acid via cytoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Clinically, AKBA and KBA are comparable with sulfasalazine and mesalazine for the treatment of Crohn's disease and ulcerative colitis, without exerting the adverse effects that are induced by steroid hormones (9,10). Multiple mechanisms responsible for their anti-inflammatory activity have been investigated, such as the NF-kB and MAPK pathways (11)(12)(13), as well as effector molecules 5-and 12-lipoxygenase (14,15), human leukocyteelastase (HLE) (16), human cathepsin G (17), mPGES-1 (18), and COX-1 (19). In our previous investigation and others' studies, a series of KBA and AKBA derivatives were obtained by the microbial transformation or chemical approaches (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 98%
“…Clinically, AKBA and KBA are comparable with sulfasalazine and mesalazine for the treatment of Crohn's disease and ulcerative colitis, without exerting the adverse effects that are induced by steroid hormones (9,10). Multiple mechanisms responsible for their anti-inflammatory activity have been investigated, such as the NF-kB and MAPK pathways (11)(12)(13), as well as effector molecules 5-and 12-lipoxygenase (14,15), human leukocyteelastase (HLE) (16), human cathepsin G (17), mPGES-1 (18), and COX-1 (19). In our previous investigation and others' studies, a series of KBA and AKBA derivatives were obtained by the microbial transformation or chemical approaches (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 98%
“…The AKBA potently suppressed the formation of 12-LOX products in intact human platelets with higher potency for p12-LOX in cell-free assays as compared to crude 5-LOX. 132 Recently, Siemoneit et al 133 reported that AKBA potently inhibits the activity of COX-1 enzyme in intact human platelets as well as in cell free assays, whereas COX-2 enzyme was inhibited less efficiently.…”
Section: Boswellic Acidsmentioning
confidence: 98%
“…Although previous reports demonstrated a selectivity of BAs for 5-LO, we recently showed that AKBA 89 potently suppresses 12-LO product formation, with even higher potency in cell-free assays (IC 50 = 15 mM) as compared to 5-LO (IC 50 = 50 mM) [167]. The direct interaction of AKBA 89 with platelet 12-LO was visualized by a protein fishing approach using immobilized KBA as bait and platelet lysates as protein source, where 12-LO was specifically precipitated [167].…”
Section: Pentacyclic Triterpenesmentioning
confidence: 99%